ANALISA DAN PERANCANGAN SISTEM INFORMASI MANAJEMEN ASET TETAP BERBASIS WEB PADA PT. PUTRI & DAFFA - Ripqi Saipuloh, - (2018)
PT. Putri & Daffa is one of the company of convection pants and women's wear. Production process conducted by PT. Putri & Daffa is cutting material and sewing pants and underwear. Wealth owned by PT. Putri & Daffa should be well managed to support the business processes that occur in the company. The condition of the company is currently in managing the company's assets are still experiencing many problems. The first problem faced by PT. Putri & Daffa is the management of company asset data still manual using physical document. In addition, PT. Putri & Daffa has not been able to manage the company's assets properly because PT. Putri & Daffa have not done the asset management documentation. The calculation of depreciation is not done automatically so the company does not know the value of current assets. Then the last problem faced has not been standardized asset inventory data at PT. Putri & Daffa. To overcome some of these problems will be built an asset management information system that can help PT. Putri & Daffa to perform the asset data management there. The result of the construction of an Asset Management Information System is the system can solve the problem of data management which automatically and standardization of the data.